Applications of complex systems science to address public policy issues - Simoyama, Felipe de Oliveira (2018)
In public policies, agents are part of an emergent and complex context, reason for which their actions should not be examined in isolation. The state of an agent is influenced by the state of others, in an environment where feedback is continuous and full of interactions. These characteristics result in a system where the total is more unpredictable and dazzling than the mere sum of its parts. As a result, there are a growing number of studies that use typical methods of complex systems to analyze public policies in various areas, such as healthcare, education, crime prevention, energy resources and others. Moreover, such distinct approach allows for more accessible investigations of public policy models, including policies that were not evaluated ex ante from the traditional lenses. This research had two main objectives: to verify how complex systems apply to the context of public policies theoretically and to present a practical application of a model, which was built based upon a case study. Since there is not a clear comprehension on how complex systems could benefit policy makers, this study presents, in its first part, a systematic literature review including some existing applications and the benefits of complexity science in the policy arena. On the whole, it can be asserted that there is a strong consensus that complex systems can be highly beneficial for policy makers and, consequently, for the overall population. Researchers perceive different benefits, such as the opportunity of testing policies a priori, the possibility of comparing different policies for the same topic, and the contemplation of new ideas and insights for better policy formulation. Although there are several simulations and models proposed for public policies in several areas, it lacks an empirical demonstration that effectively proves the benefits of applying complex systems in public policies, i.e., apparently, there are obstacles that prevent such models from having effects in the real world. In this way, the second part of the research presents an agent-based model that can be applied empirically in a government agency: a regulatory body. Such model allows policy makers to compare different enforcement strategies and anticipate side effects that would be difficult to predict without the use of simulations. In this sense, the objective of the second part of this research was to build an agent-based model of a public policy and for which a practical implementation could be carried out. Therefore, a public policy from a professional regulatory board in the healthcare area was chosen, for which two different strategies were tested, with the objective of comparing their efficiency and effectiveness. Such strategies were modeled and simulated with the use of Netlogo software with different scenarios. Results indicate that agent based models can serve as predictive tools for comparing and improving inspection strategies, and also as source of insights for anticipating unintended consequences that would hardly be noticed ex ante without the use of simulation tools